"Girls will be served until you have to carry them out": Gendered serving practices in Oslo. (2nd January 2016) - Buvik, Kristin; Baklien, Bergljot
Abstract: Research on heavy drinking among women implies that this behaviour is deviant and criticised by society, which would suggest that intoxicated women are more likely than men to be denied alcohol at drinking establishments. However, a recent Norwegian study shows that it is more likely for intoxicated women than intoxicated men to be served alcohol. This article explores gender differences and overserving within licensed establishments. The data consist of qualitative interviews with bartenders and pseudo-patrons. The latter were actors who were seemingly intoxicated while attempting to purchase alcohol at drinking establishments. Our analysis suggests that there are three main reasons why alcohol is served to intoxicated women. First, female patrons are profitable for drinking establishments because their presence causes male patrons to remain at the venue and spend more money. Second, female patrons are regarded as being sexually available to other patrons and staff in the barroom, which is a heavily sexually charged scene. Third, female patrons are considered harmless and their presence even dampens male aggression. In contrast to these explanations, there is some concern for the safety of intoxicated women. The night-time economy in Oslo seems to combine a strictly gendered perception of male and female patrons with a new acceptance of female binge drinking. The overserving of female patrons can be regarded as a consequence of the combination of these two seemingly contradictory tendencies.